Challenges in the Diagnosis and Management of Spontaneous Rectus Sheath Haematoma in Pregnancy: A Case Report - Adibah Mohd Lot; Rashidah Mohamad Khalid; Razrim Rahim (Gazi University Faculty of Medicine, 2024)
Indexed by WOS/Scopus/ERA